Application Research on Wireless Communication Private Network of Distrbution Power Grid for Special Areas - Zhihua Guo; Xiaohui Xue; Na Li; Jiangfei Wan; Ping Chen; Xi Lin; Qinfeng Jing (Dianxin kexue)
The research in wireless communication network construction and application for power grid distribution and consumption were focused on. The needs and urgency of wireless network construction in the less complex areas were analyzed. The function，performance and economical requirement of the power grid wireless network was explored，including the comparison of common kinds of wireless network combining the needs of distribution and consumption in power grid. LTE230 system has been recommended for power grid wireless communication network. As the result，the way of construction and application model for promoting the social stability and harmonious sustainable development was given.